2017
DOI: 10.1038/srep46157
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and genomic analyses of two newly isolated Morganella phages define distant members among Tevenvirinae and Autographivirinae subfamilies

Abstract: Morganella morganii is a common but frequent neglected environmental opportunistic pathogen which can cause deadly nosocomial infections. The increased number of multidrug-resistant M. morganii isolates motivates the search for alternative and effective antibacterials. We have isolated two novel obligatorily lytic M. morganii bacteriophages (vB_MmoM_MP1, vB_MmoP_MP2) and characterized them with respect to specificity, morphology, genome organization and phylogenetic relationships. MP1’s dsDNA genome consists o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Furthermore, it was found that isolated phages have a wide host range among MDRSA isolates collected from different clinical sites, both from inpatients and outpatients which is in accordance with other staphylococcal K-like phages [9,16,18]. Though it was proven that selected spot test method, when spotting high titer lysates (10 9 PFU/mL), can generate false positive results correlated with abortive infection, lysis from without, and enzyme activity [48] it is still used to screen the bactericidal ability of the isolated phages [25,49,50]. Moreover, applying phages at lower concentrations prevents from the overestimation of phage sensitivity [51].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, it was found that isolated phages have a wide host range among MDRSA isolates collected from different clinical sites, both from inpatients and outpatients which is in accordance with other staphylococcal K-like phages [9,16,18]. Though it was proven that selected spot test method, when spotting high titer lysates (10 9 PFU/mL), can generate false positive results correlated with abortive infection, lysis from without, and enzyme activity [48] it is still used to screen the bactericidal ability of the isolated phages [25,49,50]. Moreover, applying phages at lower concentrations prevents from the overestimation of phage sensitivity [51].…”
Section: Discussionmentioning
confidence: 98%
“…Transmission electron microscopy. Transmission electron micrographs (TEM) of phage Stuart were captured using a JEM-1400 microscope (JEOL, Tokyo, Japan) exactly as previously described (44). Lysates were centrifuged (1 h, 25,000 ϫ g, 4°C) to pellet phages and then washed twice with tap water.…”
Section: Methodsmentioning
confidence: 99%
“…RBP phage-encoded enzymes. Tailed phages of both Gram-negative and Gram-positive bacteria commonly harbour peptidoglycan-degrading enzymes, including endopeptidases 81 , N-acetylmuramyl-l-alanine amidases 82 , N-acetylglycosaminidase 83,84 , lysozymes 85 and lytic transglycosylases 86 . These enzymes locally degrade or rearrange peptidoglycan 87 , and although they are not always required for infection, they provide advantages under particular conditions.…”
Section: Phage Tail-like Complexesmentioning
confidence: 99%